Thermal Performance Improvement of Modified Hemispherical Cavity Receiver with Air Curtain. Issue 1 (1st October 2022) - Simer, Abhishek; Maurya, Akanksha; Kumar, Anoop
Abstract: Heat losses from solar cavity receivers degrade the efficiency of solar parabolic dish collector system. Specifically, increased convection losses emulate a significant contribution in decreasing the performance of the modified solar cavity receiver and hence, reducing these convection losses has become a matter of great concern. The Air curtain plays a crucial role in minimizing the convection losses. This work proposes an air curtain-based modified cavity receiver wherein a plane nozzle is placed on the face of receiver to produce air curtain effect. Air curtain will prevent hot air from escaping the modified cavity receiver and increase the stagnation zone inside it to reduce natural convection on the surfaces. Numerical analyses are performed considering different air velocities and receiver orientations to evaluate the effect of air curtains on the convection losses. The impact of plane air nozzle parameters like outlet temperature, inclination, and outlet velocity of the nozzle on convection losses are shown and these parameters' optimal value is evaluated. Our results state that the air curtain attached to the modified solar cavity receiver significantly improves performance by reducing the convection losses.